Can Anyone Hear Us? An Exploration of Echo Chambers at a Land-Grant University - Taylor K Ruth; Joy N Rumble; Sebastian Galindo-Gonzalez; Lisa K Lundy; Hannah S Carter; Kevin M Folta (Journal of Applied Communications, 2019)
Faculty at land-grant universities are expected to engage in some form of Extension, or science communication, as part of the land-grant mission. However, critics have claimed these institutions are out of touch with their stakeholders’ needs and faculty mainly communicate with others in academia. This engagement with a homogenous group reflects the concepts of echo chambers, where people are only exposed to information that aligns with their beliefs and current knowledge and discredit opposing information. An explanatory mixed-methods design was used to understand land-grant faculty’s engagement in echo chambers. A survey was distributed to a census of tenure-track faculty in the University of Florida’s Institute of Food and Agricultural Sciences to understand respondents’ engagement in echo chambers. Follow-up interviews were conducted with 13 of the survey respondents to further explore their audiences and channels used in science communication to understand their engagement in echo chambers. Survey results indicated faculty did not necessarily participate in echo chambers, but they also did not contribute to an open communication network. However, the interviews found participants were interested in reaching new audiences yet struggled to communicate with stakeholders. The participants also reported wanting to find alternative channels to peer reviewed journals to help disseminate their work. The findings from this study indicated faculty contributed to a type of echo chamber, but rather than viewing their stakeholders’ opinions as false, they simply did not hear the opinions. Agricultural communicators should work with land-grant faculty administrators to identify appropriate audiences and channels for science communication.
Keywords: Science Communication; Echo Chambers; Land-grant universities